PSYCHOLOGICAL CHARACTERISTICS OF TEACHER-STUDENT RELATIONSHIPS IN THE FORMATION OF STUDENTS' COMPETENCIES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This paper explores the psychological dimensions of teacher-student relationships and their influence on the development of key competencies among students in the context of modern education. Effective communication, emotional support, mutual respect, and psychological safety are essential components of a healthy teacher-student interaction that contributes significantly to both academic success and the holistic development of students. The study highlights how the quality of this relationship can shape students’ cognitive, emotional, and social competencies, including critical thinking, collaboration, adaptability, and self-regulation. It also discusses psychological theories and pedagogical models that explain how interpersonal dynamics between teachers and learners affect motivation, engagement, and identity formation. Furthermore, the paper addresses practical strategies for educators to foster psychologically supportive learning environments that promote student growth and competency formation.